Tailoring the structure and gas permeation properties of silica membranes via binary metal oxides doping. Issue 101 (29th September 2015) - Ngamou, P. H. Tchoua; Ivanova, M. E.; Herwartz, C.; Lühmann, N.; Besmehn, A.; Meulenberg, W. A.; Mayer, J.; Guillon, O.
Abstract : The incorporation of binary Co–Mn or Co–Cr oxides within the silica matrix leads to the formation of silica structures with different networks, which allows tuning of the gas separation properties. Abstract : The sol–gel method was employed for the synthesis of binary X–Co (X: Mn, Cr) oxide-doped silica membranes with different X/Co molar ratios (X/Co: 0.1, 0.3, 0.9). Single-gas permeation tests were performed at 200 °C to determine the effect of the binary oxide composition on the amorphous silica network. The X-ray diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS) and Transmission Electron Microscopy (TEM) indicated the presence of smaller Mn x Co3− x O4 and Cr x Co3− x O4 oxide nanocrystals in the silica matrix in addition to amorphous Co, Mn and Cr species. The H2 /N2 permeance ratio decreased from (126.3 ± 9) to (10.7 ± 2) with an increase in X/Co molar ratio from 0.1 to 0.9 due to the formation of larger pores. However, the binary Co–X oxide-doped silica membrane with the lowest X content showed a H2 /N2 permeance ratio, (126.3 ± 9), higher than that, (63.6 ± 6), of the single cobalt oxide silica membrane. Based on FTIR analysis, it was found that the densification of the membrane at low X content resulted from the formation of silica structures with narrowed siloxane rings. In contrast, the enlargement of siloxane rings due to favorable condensation reactions occurred at high X content.